Employees perceptions of the importance of human resources management practices - Cesário, Francisco José Santos (2016)
Increased research has been focused on establishing positive effects of HR practices on behaviors outcomes and firm performance and less attention has been taken to the perceptions of employees about the importance of the HR management practices on their professional development and career success. In particularly, we wanted to understand these perceptions under a deep economic and labor recession context, such as the one in Portugal between 2010-2014. With this assumption, our study aims to present an instrument that accurately captures employees’ perceptions of the importance of Human Resources management practices promoted by organizations. Based on literature, a written questionnaire was developed and data from 525 Portuguese workers were collected between November 2013 and January 2014. Validity of the questionnaire was analyzed and its results confirmed the existence of seven HR practices integration, training, performance management, career management, internal communication, rewards and celebration-demonstrating the questionnaire’ construct validity. Perceptions about each of the Human Resources management practices by employees were found to be positively related to global perception of HR activities, however perceptions showed a low valuation of the practices. These results encourage addressing the gap in literature with adequate measures from the point of view of employees‘ perceptions about the importance of HR activities in the Portuguese context.